Using Intervention Mapping to Develop Health Education and Health Policy Components to Increase Breast Cancer Screening and Chemotherapy Adherence Among Syrian and Iraqi Refugee Women in Beirut, Lebanon - Sacca, Lea; Markham, Christine; Fares, Johny (Frontiers in Public Health, 2020)
Abstract Introduction: Despite the continuous increase in the incidence of metastatic breast cancer among Syrian and Iraqi refugee women residing in camp settings in Lebanon, mammography and chemotherapy adherence rates remain low due to multiple social, economic, and environmental interfering factors. This in turn led to an alarming increase in breast cancer morbidity and mortality rates among the disadvantaged population. Methods: Intervention mapping, a systematic approach which guides researchers and public health experts in the development of comprehensive evidence-based interventions (EBIs) was used to plan a health education and health policy intervention to increase breast cancer screening and chemotherapy adherence among Iraqi and Syrian refugee women aged 30 and older who are residing in refugee camps within the Beirut district of Lebanon. Results: The generation of the logic model during the needs assessment phase was guided by an extensive review of the literature and reports published in peer-reviewed journals or by international/local organizations in the country to determine breast cancer incidence and mortality rates among refugee women of Syrian and Iraqi nationalities. The underlying behavioral and environmental determinants of the disease were identified from qualitative and quantitative studies carried out among the target population and also aided in assessing the sub-behaviors related to the determinants of breast cancer screening and chemotherapy completion as well as factors affecting policy execution to formulate performance objectives. We then developed matrices of change objectives and their respective methods and practical applications for behavior change at the intrapersonal, interpersonal, organizational, and societal levels. Both educational components (brochures, flyers) and technological methods (videos disseminated via Whats app and Facebook) will be adopted to apply the different methods selected (modeling, self-reevaluation, consciousness raising, persuasion, and tailoring). We also described the development of the educational and technological tools, in addition to providing future implementers with methods for pre-testing and pilot-testing of individual and environmental prototype components. Conclusion: The use of intervention mapping in the planning and implementation of holistic health promotion interventions based on information collected from published literature, case reports, and theory can integrate the multiple disciplines of public health to attain the desired behavioral change.